Oligoadenylate synthetase-like aggravated Newcastle disease virus–induced necroptosis in glioma cells - Yu, Zecheng; Chen, Yuxin; Chen, Sisi; Ye, Wenjing; Li, Ruirui; Fu, Yutang; Chen, Yangkun; Fu, Wenhao; Wei, Xianqiao; Yu, Qin; Cai, Yili; Wang, Lingyun; et al. (Frontiers in Oncology, 2025)
BackgroundNewcastle disease virus (NDV) has emerged as a tumor-lysing agent in a variety of cancers. Previous studies have shown that NDV has cytolytic activity in gliomas; however, the underlying mechanisms have not been fully elucidated.MethodsComparing the glioma cells LN229 controlled group with the infected group of NDV rLa Sota-GFP strain, we strive to observe the changes in the genome and protein levels as well as the activation of the signalling pathways before and after the infection at the cellular level and at the level of the genes in the transcriptome, to study the molecular mechanism of necroptosis of the NDV-infected lethal LN229.ResultsWe found that NDV infection which inhibited glioma cells LN229 proliferation and promoted apoptosis in a dose-dependent manner involved mitochondrial disruption by a molecular mechanism, whereas the Fe2+ assay didn’t change. Additionally, the necroptosis inhibitor Nec-1 alleviated the cellular damage caused by NDV during infection of LN229 cells. Using RNA-seq analysis, the necroptosis pathway was significantly enriched in NDV-infected LN229 cells, and the antiviral gene OASL (Oligoadenylate synthetase-like) was significantly up-regulated in the apoptotic signalling pathway, which could be directly induced by NDV infection. Knockdown of OASL attenuates NDV infection-induced necroptosis in LN229 cells.ConclusionOur study demonstrates that NDV has cytolytic activity on glioma cells by inducing necroptosis. Additionally, targeting upregulation of OASL may provide a novel strategy to enhance necrotic apoptosis in glioma cells after NDV infection.